ARTIFICIAL INTELLIGENCE SEBAGAI ENABLER TECHNOPRENEURSHIP DALAM PENGUATAN EKOSISTEM DIGITAL UMKM KOPERASI - Harun AS; Muhammad Helmi; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
Digital transformation driven by national policies, including Presidential Instruction No. 3 of 2021 and Presidential Regulation No. 2 of 2024 on the National Artificial Intelligence Strategy, has reshaped the entrepreneurial landscape, particularly for Micro, Small, and Medium Enterprises (MSMEs). This transformation has encouraged the development of technopreneurship by positioning technology as a primary source of value creation and competitive advantage. Although Artificial Intelligence (AI) has been prioritized as a strategic technology in Indonesia’s digital transformation agenda, existing studies predominantly conceptualize AI as a technical tool rather than an entrepreneurial capability that shapes technopreneurial orientation and behavior. This study aims to analyze the role of AI as an enabler of technopreneurship in strengthening the digital ecosystem of cooperative-based MSMEs through a holding approach. A conceptual research design employing a systematic synthesis of the literature on technopreneurship, artificial intelligence, dynamic capabilities, MSME holdings, and digital ecosystems was applied. The findings indicate that AI functions as a collective entrepreneurial capability that strengthens sensing, seizing, and transforming capacities in business development. The integration of AI within holding schemes and digital ecosystems enables MSMEs to enhance collaboration, operational efficiency, innovation, and sustainable competitiveness.